Bless. 1 - Sonoyama, Yukino (Kodansha, 2024)
"At a young age, Aia Utagawa was scouted as a model, but his real ambition is to become a makeup artist. But, even as the end of high school approaches, it's a dream he hides inside, afraid of stepping outside his prescribed role as a pretty face. Then, one day, he meets Jun, a quiet classmate who hunches because she's ashamed of her face, covered in freckles. He convinces her to enter a school runway fashion contest together--with him doing her makeup. They make an incredible team, with Jun discovering a confidence she never knew she could show and Aia finally learning that, while it may be tough to open yourself up to failing at the one thing you care about, the difficulties can be worth facing."--Amazon.com.